Penguatan Ekosistem Wisata Berkelanjutan Melalui Introduksi Inovasi Agroindustri di Desa Teratak, Lombok Tengah, Nusa Tenggara Barat - Kiki Fibrianto; Susinggih Wijana; Atiek Iriany; Taufiq Ismail; Husna Atikah; Eka Shinta Wulandari (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
Teratak Village has a number of natural resources, including mangosteen, durian, and banana commodities, as well as natural tourism potential. The tourism potential of Teratak Village includes the Rinjani Geopark, Tereng Kuning, Blue Lake, Elong Tune Waterfall, and Serawah Waterfall. However, the development of tourism and UMKM is still not optimal. This is due to the lack of specific knowledge and skills in handling the tourism sector, as well as the development of MSMEs based on local potential. Therefore, this community service activity aims to improve agro-industrial management through the development of edu-ecotourism, enhance public knowledge and skills in tourism management, and develop local MSME clusters through the diversification of banana and mangosteen products as well as digital marketing. In the implementation of activities, several programs were carried out, starting with the preparation of activity schedules and targets, followed by Forum Group Discussions (FGDs) along with socialization and training. Socialization and training activities included banana and mangosteen product diversification and production management. A mapping of potential edu-ecotourism objects was obtained through the Forum Group Discussions (FGDs). The results of the program implementation were achieved through the formation of Pokdarwis and the realization of the edu-ekosiwata concept, as well as the introduction of diversified banana and mangosteen products that received a positive response from the Teratak Village community.